Stress Intensity Factor for the Interaction between a Straight Crack and a Curved Crack in Plane Elasticity - Aridi M.R.; Nik Long N.M.A.; Eshkuvatov Z.K. (Huazhong University of Science and Technology, 2023)
Cracks; Elasticity; Numerical methods; Stress intensity factors; Complex variable function; Complex variable function method; Curved crack; curved length coordinate method; Hypersingular integral equation; In-plane elasticity; Numerical scheme; Straight crack; Integral equations